Vive les bovins! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
L'Élevage de la vache laitière en zone tropicale Éditeurs scientifiques : Christian Meyer et Jean-Pierre Denis CIRAD, collection 'Techniques' La librairie du CIRAD BP 5035 34032 Montpellier cedex 1 - FRANCE 314 pages ISSN : 1275-6083 ISBN : 2-87614-33